2017
DOI: 10.1590/s1678-9946201759029
|View full text |Cite
|
Sign up to set email alerts
|

Oral Candida spp carriage and periodontal diseases in HIV-infected patients in Ribeirão Preto, Brazil

Abstract: The majority of HIV-infected patients develop Candida spp-associated clinical oral lesions. Studies have shown that asymptomatic oral colonization of Candida spp may lead to oral lesions or become a source of disseminated infections. The aim of this study was to verify the effects of periodontal conditions on Candida spp prevalence and Candida spp carriage in the oral cavity of HIV-infected patients compared to non-infected patients. Twenty-five patients not infected with HIV and 48 HIV-infected patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
42
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 34 publications
9
42
2
6
Order By: Relevance
“…Similar results were reported by Canabarro A et al in (2013) [50], since the results of their investigation showed that patients with severe chronic periodontitis are significantly more colonized, at the level of subgingival niches, by several species of Candida especially Candida albicans with respect to subjects periodontally healthy. However, contrary to our results and those of Urzua B et al, and Canabarro A et al, Laurenҫo A et al (2017) [14] did not find significant differences in the frequency of recovery of Candida parapsilosis complex between immunocompetent subjects with periodontal disease vs healthy. Results similar to those of Laurenco et al in Brazil are reported by Peters B et al [48]in this same year in USA, demonstrating that subjects with periodontal disease, although, are more colonized and show a higher relative abundance of Candida species with respect to periodontally healthy subjects, however the differences were not significant either.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similar results were reported by Canabarro A et al in (2013) [50], since the results of their investigation showed that patients with severe chronic periodontitis are significantly more colonized, at the level of subgingival niches, by several species of Candida especially Candida albicans with respect to subjects periodontally healthy. However, contrary to our results and those of Urzua B et al, and Canabarro A et al, Laurenҫo A et al (2017) [14] did not find significant differences in the frequency of recovery of Candida parapsilosis complex between immunocompetent subjects with periodontal disease vs healthy. Results similar to those of Laurenco et al in Brazil are reported by Peters B et al [48]in this same year in USA, demonstrating that subjects with periodontal disease, although, are more colonized and show a higher relative abundance of Candida species with respect to periodontally healthy subjects, however the differences were not significant either.…”
Section: Discussioncontrasting
confidence: 99%
“…Other species less frequently isolated, which have been recovered from periodontal environments and the oral mucosa, are the following: C. parapsilosis, C. dubliniensis, C. tropicalis and C. guilliermondi, among others [9][10][11][12][13][14]. However, over the last ten years, some studies have found an increasein the non-albicans Candida (NAC) recovery frequency in oral mucosa: from 10 % in 1996 [1] to 15.0% [7] in 2010, 15.4 % in 2011 [8], and 25.0% in 2017 [14] in the case of C. parapsilosis at the level of healthy Citation: María L Rodríguez, Alcira C Rosa, Jennifer G Rodríguez, María L Nastri and Virginia M Jewtuchowicz (2018) The Oral Cavity: A Reservoir that Favors Colonization and Selection of Candida parapsilosis sensu stricto Strains with High Pathogen Potential Under Conditions of Gingivalperiodontal Disease. J. Dent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement in the quality of life attributed to ART can be extended to the oral cavity due to the decrease of HIV‐related oral diseases. As HIV infection became a chronic disease, chronic oral inflammatory diseases have been a subject of great interest, especially chronic periodontitis (CP) …”
mentioning
confidence: 99%
“…In addition to bacterial infection, fungal infections can easily settle in the oral cavity of HIV‐infected individuals, due to immunological changes mediated by CD4+ T lymphocytes . Most fungal infections are caused by fungi of the genus Candida spp., which has a commensal relationship with the oral cavity, but can develop pathogenicity characteristics in immunodeficiency . Oral candidiasis is common in HIV‐infected individuals, affecting > 70% of patients with AIDS .…”
mentioning
confidence: 99%